‘We’ll All Dance each Springtime with Jack-in-the-Green’: The ‘Green Man Complex’ in Contemporary British Culture - Whitehead, Amy; Letcher, Andy (Journal for the Study of Religion, Nature and Culture, 2023)
The Green Man is a familiar image in British popular culture who is celebrated in a variety of ways, not least in an ever-growing number of festive processions in towns, villages, and cities, particularly around Beltane (May Day). Combining two scholarly voices, this article offers a survey of the Green Man image and related ritual phenomena in what we refer to as the ‘Green Man complex’. Here we address the Green Man’s role in what could be the mobilization of responses to the current ecological crisis, as well as his relationship to growing trends in dark green religion. Last, we turn our attention to the theoretical innovations that current Green Man phenomena invites: more than ‘symbolic’ or ‘representational’, the Green Man is a source for contemporary Pagan ritual religious creativity that is being used in animistic, embodied, territorializing, and reciprocal fashions to direct human attention toward the other-than-human vegetable kingdom.